2016
DOI: 10.1159/000446438
|View full text |Cite
|
Sign up to set email alerts
|

Smoking History as a Predictor of Pemetrexed Monotherapy in Patients with Non-Squamous Non-Small Cell Lung Cancer

Abstract: Background: Pemetrexed monotherapy has come to be recognized as the standard of care for second-line therapy of non-squamous non-small cell lung cancer (NSCLC). Thymidylate synthase (TS) expression is recognized as a potential predictor of the response to pemetrexed-based chemotherapy in patients with advanced NSCLC. The purpose of this study was to identify useful predictors of the response to pemetrexed other than TS expression. Methods: The records of non-squamous NSCLC patients without driver mutations who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
7
1
Order By: Relevance
“…In previous studies, the adverse outcomes of smokers in chemotherapy have been confirmed. The study conducted by Igawa et al [50] showed that smoking history was a favorable predictor of efficacy of pemetrexed monotherapy in NSCLC, and long-term smoking history is associated with poor efficacy. After treatment with cisplatin, adverse outcomes of patients with testicular cancer were associated with smoking history [51].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the adverse outcomes of smokers in chemotherapy have been confirmed. The study conducted by Igawa et al [50] showed that smoking history was a favorable predictor of efficacy of pemetrexed monotherapy in NSCLC, and long-term smoking history is associated with poor efficacy. After treatment with cisplatin, adverse outcomes of patients with testicular cancer were associated with smoking history [51].…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 , 21 ] Smoking status also affects the response to conventional chemotherapy, with nonsmokers achieving better response rates to pemetrexed than smokers. [ 22 ] Nevertheless, the predictors of response to EGFR-TKI remain controversial. [ 23 ] Therefore, improving the prediction of the efficacy of EGFR-TKI drugs is a current problem needing to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…Our data was consistent with that of Igawa et al . in which smoking status was used as a predictor for pemetrexed chemotherapy regimens in wild‐type NSCLC patients . A possible explanation for the relationship between smoking status and survival is the expression of thymidylate synthase (TS).…”
Section: Discussionmentioning
confidence: 99%